Horner's syndrome and fever: An unusual presentation of the giant cell arteritis - L Marzano; PF Ballerini (Archives of Clinical Hypertension - Peertechz Publications, 2019)
The authors present a case of a histologically confirmed giant cell arteritis that presented unusually with fever and Horner's syndrome. The aetiology of the presenting features and the treatment choices are discussed.